A STUDY OF PEDAGOGICAL TERMINOLOGY IN KARAKALPAK AND ENGLISH LINGUISTICS - Sultanova, Dilfuza Kamalovna (SCIENCE and SOCIETY, 2026)
The article comparatively analyzes the formation, development, and study of pedagogical terminology in Karakalpak and English linguistics. The lexico-semantic features of pedagogical terms, their place in the education system, and their significance in scientific communication are highlighted. The history of the formation of pedagogical terminology in the Karakalpak language, the works of scientists who studied it, and terminological dictionaries are analyzed. Furthermore, the international nature of pedagogical terminology in English and the usage characteristics of terms borrowed from Greek and Latin will be examined. The research results demonstrate the importance of systematizing, standardizing pedagogical terminology in the Karakalpak language, and deepening comparative linguistic research.